A sintering and preparation method of lithium manganese iron phosphate positive electrode material and positive electrode sheet
By using spray materials with different carbon content in lithium manganese iron phosphate positive electrode material to build a three-layer structure and inject CO2 gas, the problem of poor carbon coating effect in large-scale production is solved, and the uniformity of carbon coating is achieved and The improvement in electrical performance reduces the performance differences between small batches and large batches of production.
Patent Information
- Application Number
- CN202411378029.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-30
AI Technical Summary
When the existing lithium manganese iron phosphate positive electrode material is sintered in large-scale production, the carbon coating effect is poor, resulting in a decline in electrical performance. The performance differences between small-batch tests and large-scale production are large, which affects the normal production of the process assembly line.
Spray material A and spray material B with different carbon contents are used to construct a three-layer structure and sinter it in the casing, and CO2 gas is introduced during the sintering process to remove free carbon and ensure the uniformity and density of carbon coating.
The carbon coating effect of lithium manganese iron phosphate positive electrode material is improved, the free carbon content is reduced, the electrical performance is close to small batches and large batches is produced, performance deviation is avoided, and the capacity and processing performance of the material are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a sintering and preparation method of a lithium manganese iron phosphate positive electrode material and a positive electrode sheet. Background Art
[0002] As an "upgraded version" of LFP, LMFP inherits the advantages of LFP such as low cost, high thermal stability, and high safety, and makes up for its shortcomings such as low energy density and poor low-temperature stability. However, LMFP also has problems such as poor conductivity, rate performance, and cycle performance. Therefore, carbon coating is widely used in the industry to effectively improve the conductivity and cycle performance of materials. The use of carbon-coated materials can construct a conductive network on the surface of lithium manganese iron phosphate materials, increase the conductivity of the material and the rate performance of the battery. In addition, carbon coating can effectively prevent the further growth of lithium manganese phosphate particles and prevent the corrosion of HF in the electrolyte on the positive electrode material, thereby improving the cycle performance of the positive electrode material.
[0003] Therefore, it is important to choose the right carbon content in the carbon coating process. Too high a carbon content will increase the specific surface area of the material, increase the free carbon on the surface of the material, and reduce the material processing performance, which will eventually lead to a decrease in LMFP capacity and poor cycle performance. Too low a carbon content will result in incomplete carbon coating of the lithium manganese iron phosphate material, and some lithium manganese iron phosphate particles will not be coated with carbon, which will reduce its electronic conductivity, increase the internal resistance of the battery, increase polarization, and reduce cycle performance.
[0004] On the other hand, in addition to the appropriate carbon content, the effective coating of lithium manganese iron phosphate with a carbon layer is the key to improving the electronic conductivity of the lithium manganese iron phosphate material.
[0005] In the solid phase sintering carbon coating process, the inventors found that after sintering, the same carbon coating was obtained in the test. There was a big difference in the electrical properties of the positive electrode materials in the small batch test stage and the large batch process production stage, even if the same sintering process and the same carbon coating amount were tested. After large-scale production, its electrical properties were significantly inferior to those measured in the test stage.
[0006] After the inventor explored the entire sintering process, it was found that after high-temperature sintering, the carbon content of the upper, middle and lower layers of the sagger of the spray material with the same carbon content was significantly different, often with the highest carbon content in the upper layer, the lowest carbon content in the middle layer, and the carbon content in the bottom layer being between the two. With the increase in the amount of sintering, the amount of spray material in a single sagger increases during industrial production, which makes the difference between the upper, middle and lower carbon layers more obvious. In actual production, all the sintering spray materials in the sagger are often batch-mixed and then the carbon content is tested, which in turn makes the tested carbon content meet the requirements, but the coating effect is often greatly discounted. As a result, the actual carbon coating amount of the sintered material is quite different from the tested carbon coating amount, and there is a large amount of free carbon in the sintered material system. As the amount of sintered material increases, the gap in the aforementioned carbon coating amount also increases, and the stock of free carbon also increases, which results in the electrical properties measured in the small batch test stage being significantly better than the electrical properties in the large batch industrial production stage. However, the current sintering method will produce a large amount of free carbon, which greatly reduces the carbon coating effect of the sintered product and has a huge impact on the electrical properties of lithium manganese iron phosphate positive electrode materials. Summary of the invention
[0007] The purpose of the present invention is to provide a method for sintering lithium manganese iron phosphate positive electrode materials, by regulating the sintering process, controlling the carbon coating uniformity of the sintered material, and solving the problem that the tested carbon content falsely meets the standard but the actual carbon coating effect is poor.
[0008] On the other hand, a method for preparing a lithium manganese iron phosphate positive electrode material sintered by the above sintering method and a positive electrode plate are also provided.
[0009] One is a method for sintering a lithium manganese iron phosphate positive electrode material, comprising preparing a spray material A and a spray material B with different carbon contents, wherein the carbon content of the spray material B is higher than the carbon content of the spray material A;
[0010] A three-layer structure is constructed in the sagger, with spray material B as the middle layer and spray material A as the surface layer and the bottom layer, wherein the weight distribution of the surface layer, middle layer and bottom layer materials in the sagger is the same. Then the sagger is sent to sintering;
[0011] CO2 gas is introduced during the sintering process.
[0012] On the one hand, by matching spray materials with different carbon contents, spray materials A and spray materials B are formed into a three-layer paving structure in the sintering sagger to overcome the problem that during sintering, due to the large amount of heat released by lithium iron manganese phosphate during the generation process, the reaction heat is accumulated in the middle material layer, causing the carbon in the middle layer to be taken away to the surface layer, and the middle layer forms large particles, resulting in incomplete carbon coating of lithium iron manganese phosphate in the middle layer due to the loss of the middle carbon source. This effectively avoids the problem of low capacity of lithium iron manganese phosphate in the middle layer of the sagger during sintering.
[0013] On the other hand, although a three-layer laying structure for sintering is constructed in the sagger, the lithium iron manganese phosphate in the middle layer of the sagger effectively avoids the reduction of the carbon content of the carbon coating and avoids incomplete carbon coating; however, during the sintering process, the carbon source of the middle layer will gradually move upward to the surface layer, and after the lithium iron manganese phosphate on the surface layer completes the carbon coating, the floating carbon source will gradually form a large amount of free carbon that is not coated on the surface of the lithium iron manganese phosphate particles. Therefore, in addition to blasting protective gas during the sintering process, the present application also introduces CO2 gas. In this way, with the introduction of CO2 gas, the CO2 gas is continuously in contact with the sintering material on the surface of the sagger, and the free carbon formed by floating from the middle layer of the sagger to the surface during the sintering process is removed by using CO2 gas.
[0014] In this way, by forming a three-layer structure consisting of spray material A and spray material B in the sagger, even in the process of large-scale industrial production, the uniformity of the carbon content of the upper, middle and lower layers of the lithium manganese iron phosphate in the sagger can be ensured after the sintering is completed. Therefore, it can not only ensure that after the sintering is completed, the lithium manganese iron phosphate material in the entire sagger can be effectively coated with carbon, thereby improving the coating effect of the carbon source on the lithium manganese iron phosphate; and after improving the sintering method, it is effectively avoided that the material performance obtained from the small batch test and the performance of the large batch industrial production material have a large deviation.
[0015] In some embodiments, the carbon content of the spray material A and the carbon content of the spray material B differ by 0.1% to 1%.
[0016] This prevents the carbon content difference between spray material B and spray material A from being too large, which affects the uniformity of the carbon content of the layers of the final sintered product. At the same time, it also prevents the carbon content difference between spray material B and spray material A from being too small, which causes the carbon content of the lithium iron manganese phosphate materials in the middle layer and the surface layer to be too low after sintering. Moreover, if the carbon content difference between spray material B and spray material A is too small, the carbon source of the middle layer will escape with the heat during the sintering process and transfer to the upper layer, resulting in an increase in the carbon source of the upper layer, because under certain sintering temperature conditions, the amount of carbon escaping from the middle layer remains basically unchanged. Therefore, in order to ensure that the carbon sources of the upper, middle and lower layers in the sagger are basically the same, the carbon source of the middle layer has a certain difference from the previous carbon source, resulting in an increase in the difference in the carbon source content of the lithium iron manganese phosphate material in the sagger, and the carbon coating effect of the above two layers is poor.
[0017] In some embodiments, the CO2 gas is blown in at the end of the sintering process, and one of nitrogen, argon or helium is used as a protective gas throughout the sintering process.
[0018] Among them, nitrogen, argon or helium as protective gas provides a stable sintering environment for the entire sintering environment to avoid oxidation of the sintering materials in the early stage of sintering. As the sintering process proceeds, at the end of sintering, as mentioned above, a large amount of free carbon will be generated on the surface of the sagger material. At this time, while ensuring the continuous supply of protective gas at the end of sintering, CO2 gas is blown in to use CO2 gas in the protective gas environment to remove the free carbon generated on the surface of the material.
[0019] Moreover, in some embodiments, according to the actual sintering needs and the difference in carbon content between spray material A and spray material B, during the sintering process, when CO2 gas needs to be blown in, the volume ratio of the aforementioned CO2 gas to the protective gas is 1:1 to 9. Thus, by controlling the content of CO2 in the sintering system, on the one hand, it is avoided that CO2 reacts with the surface material to destroy the carbon layer uniformly and densely coated on the surface of the lithium manganese iron phosphate, and on the other hand, it is avoided that CO2 reacts incompletely with the surface material, resulting in a large amount of free carbon remaining on the surface of the lithium manganese iron phosphate material on the surface of the sagger.
[0020] Meanwhile, in other embodiments, in addition to controlling the content of CO2 gas in the sintering environment, the final stage of the entire sintering reaction, that is, the removal process of free carbon, can also be adjusted by adjusting the blowing time of CO2 gas. Preferably, the cumulative blowing time of CO2 gas is 2 to 6 hours.
[0021] In some embodiments, in the aforementioned sintering process, after the sagger is filled with materials to form a three-layer paving structure, it is placed in a sintering device for sintering, and the preferred temperature is 650-850°C, and the total sintering time is 7 to 12 hours. Among them, the total sintering time here includes the aforementioned cumulative time of CO2 gas injection. In order to avoid the influence of CO2 gas on the normal carbon coating process of lithium manganese iron phosphate on the surface of the sagger during the sintering process, the timing of the injection of CO2 gas is the last 2 to 6 hours of the total sintering time of 7 to 12 hours.
[0022] In summary, for the sintering method involved in this application, on the one hand, by laying the lithium iron manganese phosphate spray material in three layers, the problem of incomplete coating and poor carbon coating effect of the lithium iron manganese phosphate material in the middle layer during the sintering process is avoided. On the other hand, by blowing CO2 gas into the sintering environment in the later stage of sintering, the problem of a substantial increase in free carbon on the surface of the material caused by the three-layer material laying is overcome. Therefore, by improving the sintering process, not only can the uniformity and density of the carbon coating of the entire lithium iron manganese phosphate after sintering be improved; at the same time, the free carbon content of the broken material after sintering can be effectively reduced, and the capacity of the lithium iron manganese phosphate positive electrode material can be effectively increased.
[0023] Secondly, the present application also provides a method for preparing a lithium manganese iron phosphate positive electrode material.
[0024] Take the LiMn x Fe (1-x) Iron source, manganese source, lithium source, doping source and carbon source in stoichiometric ratio of PO4 (0.1≤x≤0.9) are put into a ball mill, and then transferred into a spray tower for spraying. By adjusting different carbon source contents, spray material A and spray material B are prepared respectively. As mentioned above, the carbon content of spray material A is lower than that of spray material B.
[0025] Then, the spray material A and the spray material B are sintered according to the aforementioned lithium manganese iron phosphate positive electrode material sintering method.
[0026] Furthermore, the lithium iron manganese phosphate positive electrode material prepared by the aforementioned sintering method can, on the one hand, increase the capacity of the entire positive electrode material by reducing the content of free carbon in the carbon-coated lithium iron manganese phosphate material. On the other hand, whether it is sintering in the test stage of a small batch or sintering in the industrial production stage of a large batch, after the sintering is completed, the carbon content of the lithium iron manganese phosphate at different levels in the sagger is similar, and there is less free carbon; this makes the electrical properties of the test results of the test preparation materials closer to those of the industrial production materials, and makes the actual effect of the lithium iron manganese phosphate positive electrode material after being converted from the laboratory to industrial production more accurate. Avoid huge deviations between industrial production performance and experimental test performance that affect the normal production of the process line.
[0027] In some embodiments, the carbon source used to prepare the lithium iron manganese phosphate spray material is one or more of sucrose, glucose, citric acid, polypyrrolidone, and PEG. Preferably, sucrose is used as the carbon source.
[0028] Thirdly, the present application also relates to a positive electrode plate, which is prepared using the aforementioned lithium iron manganese phosphate positive electrode material to form a positive electrode plate. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0030] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.
[0032] A method for sintering a lithium manganese iron phosphate positive electrode material, comprising preparing a spray material A and a spray material B with different carbon contents, wherein the carbon content of the spray material B is higher than the carbon content of the spray material A;
[0033] A three-layer structure is constructed in the sagger, with spray material B as the middle layer and spray material A as the surface layer and the bottom layer, wherein the weight distribution of the surface layer, middle layer and bottom layer materials in the sagger is the same. Then the sagger is sent to sintering;
[0034] CO2 gas is introduced during the sintering process.
[0035] On the one hand, by matching spray materials with different carbon contents, spray materials A and spray materials B form a three-layer paving structure in the sintering sagger, so as to overcome the problem that the lithium iron manganese phosphate material in the middle layer of the sagger releases a lot of heat during the generation process during sintering, causing a large amount of reaction heat to accumulate, resulting in the carbon in the middle layer being taken away to the surface layer, causing the middle layer to form large particles due to the loss of the intermediate carbon source, resulting in incomplete carbon coating of the lithium iron manganese phosphate in the middle layer. This effectively avoids the problem of low capacity of the lithium iron manganese phosphate in the middle layer of the sagger during sintering.
[0036] On the other hand, although a three-layer laying structure for sintering is constructed in the sagger, the lithium iron manganese phosphate in the middle layer of the sagger effectively avoids the reduction of the carbon content of the carbon coating and avoids incomplete carbon coating; however, during the sintering process, the carbon source of the middle layer will gradually move upward to the surface layer, and after the lithium iron manganese phosphate on the surface layer completes the carbon coating, the floating carbon source will gradually form a large amount of free carbon that is not coated on the surface of the lithium iron manganese phosphate particles. Therefore, in addition to blasting protective gas during the sintering process, the present application also introduces CO2 gas. In this way, with the introduction of CO2 gas, the CO2 gas is continuously in contact with the sintering material on the surface of the sagger, and the free carbon formed by floating from the middle layer of the sagger to the surface during the sintering process is removed by using CO2 gas.
[0037] In this way, by forming a three-layer structure consisting of spray material A and spray material B in the sagger, even in the process of large-scale industrial production, the uniformity of the carbon content of the upper, middle and lower layers of the lithium manganese iron phosphate in the sagger can be ensured after the sintering is completed. Therefore, it can not only ensure that after the sintering is completed, the lithium manganese iron phosphate material in the entire sagger can be effectively coated with carbon, thereby improving the coating effect of the carbon source on the lithium manganese iron phosphate; and after improving the sintering method, it is effectively avoided that the material performance obtained from the small batch test and the performance of the large batch industrial production material have a large deviation.
[0038] The present invention is described below through specific implementation methods.
[0039] Example 1
[0040] A method for preparing a lithium manganese iron phosphate positive electrode material, the specific steps are as follows:
[0041] Step 1: Take LiMn x Fe (1-x) PO4 (0.1≤x≤0.9) stoichiometric ratio of iron source, manganese source, lithium source, doping source and sucrose are placed in a ball mill, wherein the amount of sucrose is 1.0-1.5% of the mass of the finished LMFP product. Add appropriate amount of anhydrous methanol, pour into the ball mill and mix thoroughly, then transfer to a sand mill with a sand mill speed of 800rpm. When the sand mill particle size is 0.5±0.05μm, transfer to a spray tower for spraying to obtain spray material A.
[0042] Step 2: Repeat step 1, and increase the amount of sucrose to 1.5-2.0% of the mass of the LMFP finished product to obtain spray material B.
[0043] Step 3: Divide the 7.5kg sagger into three equal parts, load 2.5kg of spray material A into the bottom of the sagger, load 2.5kg of spray material B into the middle layer of the sagger, and then load 2.5kg of spray material A into the top layer of the sagger.
[0044] Step 4: Introduce nitrogen into the kiln to ensure that the oxygen concentration in the kiln is below 50ppm, place the sagger filled with spray material into the roller kiln for sintering, set the sintering temperature to 650~850℃, and set the sintering time to 7~12h.
[0045] Step 5: Introduce CO2 gas with a purity of 99.99% into the kiln, where the CO2 flow rate is half of the nitrogen flow rate. Here, the CO2 content in the sintering system is adjusted by adjusting the relationship between the flow rates of CO2 and protective gas. The cumulative time for introducing CO2 gas is 2 hours.
[0046] Step 6: After sintering is completed, take samples from the upper, middle and lower layers of the sagger and test the carbon content respectively to verify the distribution of the carbon source in the upper, middle and lower layers.
[0047] Step 7: After the sintered samples are mixed and crushed evenly, a high-capacity lithium manganese iron phosphate positive electrode material with uniform carbon coating is obtained.
[0048] Example 2
[0049] In this embodiment, compared with Embodiment 1, the difference is that the cumulative time of the introduction of CO2 gas is 4 hours.
[0050] Example 3
[0051] In this embodiment, compared with Embodiment 1, the difference is that the cumulative time of the introduction of CO2 gas is 6 hours.
[0052] Example 4
[0053] In this embodiment, compared with embodiment 2, the difference is that the sagger containing 7.5 kg is divided into three parts, wherein 2 kg of spray material A is loaded into the bottom layer, 3.5 kg of spray material B is loaded into the middle layer, and 2 kg of spray material A is loaded into the surface layer. Other conditions and steps are the same as those in embodiment 2.
[0054] Example 5
[0055] In this embodiment, compared with embodiment 2, the difference is that the sagger containing 7.5 kg is divided into three parts, wherein 1.5 kg of spray material A is loaded into the bottom layer, 4.5 kg of spray material B is loaded into the middle layer, and 1.5 kg of spray material A is loaded into the surface layer. Other conditions and steps are the same as those in embodiment 2.
[0056] Comparative Example 1
[0057] In this comparative example, the difference from Example 2 is that step 2 is removed and step 3 is modified to put all 7.5 kg of spray material A into the sagger. The remaining conditions and steps are the same as those in Example 2.
[0058] Comparative Example 2
[0059] In this comparative example, the difference from Example 2 is that step 5 is removed. The remaining conditions and steps are the same as those in Example 2.
[0060] Comparative Example 3
[0061] In this comparative example, the difference from Example 2 is that the sagger containing 7.5 kg is divided into three equal parts, wherein the bottom of the sagger is filled with 2.5 kg of spray material B, the middle layer is filled with 2.5 kg of spray material A, and the surface layer is filled with 2.5 kg of spray material B. The remaining conditions and steps are the same as those in Example 2.
[0062] Comparative Example 4
[0063] In this comparative example, the difference from comparative example 1 is that the spray material A in a single sagger is adjusted from 7.5 kg to 8.5 kg. The remaining conditions and steps are the same as those in comparative example 1.
[0064] The above-mentioned embodiments and comparative examples are tested below, and the specific testing method is as follows:
[0065] Carbon Content:
[0066] A sulfur-carbon analyzer is used to collect CO2 information generated during sample combustion through infrared spectroscopy and calculate the carbon content in the sample.
[0067] Resistivity:
[0068] After the samples were pressed into sheets, they were tested using a four-probe resistivity tester.
[0069] Specific surface area:
[0070] The specific surface area was tested by nitrogen isothermal adsorption-desorption method.
[0071] Particle size distribution:
[0072] The particle size distribution of the sample was tested using a particle size tester, and the test data D10, D50, D90 and D99 were recorded.
[0073] Charge and discharge test:
[0074] The simulated battery is tested at 23℃±2℃ according to the operating procedures of the battery charge and discharge tester to obtain the discharge specific capacity data of the simulated battery.
[0075] The specific results are as follows:
[0076]
[0077] In the above table, 1th CC refers to the first cycle of button-type lithium battery capacity in grams when the button-type lithium battery is charged with constant current (CC) until the battery is fully charged; 1th DC refers to the first cycle of button-type lithium battery capacity in grams when the button-type lithium battery is discharged with constant current (DC) until the battery is discharged; 1th eff refers to the first discharge efficiency.
[0078] From the comparison of Examples 1-5, it can be seen that by adjusting the different loading amounts of spray material A and spray material B and the duration of CO2 gas, lithium manganese iron phosphate samples with uniform carbon content in the upper, middle and lower parts can be prepared, and their corresponding resistivity is significantly reduced and the capacity is improved.
[0079] By comparing Example 2 with Example 4 and Example 5, it is found that when the sagger is unequally filled with spray material A and spray material B, the carbon content in the upper, middle and lower layers of the sagger fluctuates more. This is because the reaction heat of the material in the middle layer is more easily accumulated, and the material in the middle layer accumulates higher heat. When the higher heat in the middle layer is transferred to the upper layer, part of the carbon is brought to the surface of the sagger to form free carbon. Too much or too little amount of high-carbon-content spray material B in the middle layer will have a significant effect on the carbon content of the upper and lower layers, thereby resulting in differences in the carbon content in the upper, middle and lower layers of the sagger.
[0080] Comparing Example 2 with Comparative Example 1, it is found that the carbon content of lithium manganese iron phosphate in the upper, middle and lower layers of a single sagger meets the condition that the carbon content of the upper layer is greater than the carbon content of the lower layer and greater than the carbon content of the middle layer. However, after the materials are taken out and mixed, the carbon content detection data that meets the standards can be obtained. Example 2 adopts the method of constructing a three-layer laying structure in the sagger, and assists in introducing CO2 gas at the end of sintering. In this way, even if the sintered materials are not mixed, the carbon content of the upper, middle and lower layers of the sintered materials is directly detected, and balanced carbon content test data can be obtained, indicating that the loss of the carbon source in the middle layer is effectively avoided, and a large amount of free carbon appears on the surface.
[0081] By comparing Example 2 with Comparative Example 2, it is found that the carbon content of the upper layer decreases significantly when CO2 gas is introduced at the end of sintering. Therefore, by introducing CO2 gas at the end of sintering, a large amount of free carbon generated by the floating of the carbon source in the middle layer can be effectively reduced, thereby ensuring electrical performance.
[0082] By comparing Example 2 with Comparative Example 3, it is found that increasing the carbon content with a lower carbon content in the middle layer of the sagger increases the difference in carbon distribution in the upper, middle and lower layers, and the free carbon in the upper layer increases, resulting in a significant increase in its resistivity and a significant decrease in 0.1C discharge capacity, where 0.1C means charging and discharging at 0.1 times the battery capacity.
[0083] By comparing Comparative Example 1 with Comparative Example 4, it is found that after increasing the filling amount of a single sagger, the difference in the amount of carbon in the upper, middle and lower layers increases significantly, indicating that when the output is increased by increasing the filling amount, there is an uneven distribution of carbon sources in the upper, middle and lower layers of the sagger, and the prepared lithium manganese iron phosphate material is at risk of impaired capacity.
[0084] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for sintering lithium manganese iron phosphate positive electrode material, characterized in that: The method comprises preparing a spray material A and a spray material B having different carbon contents, wherein the carbon content of the spray material B is higher than the carbon content of the spray material A; A three-layer structure is constructed in the sagger, with the spray material B as the middle layer and the spray material A as the surface layer and the bottom layer, and the sagger is sent to sintering; CO2 gas is introduced during the sintering process; The CO2 gas is blown in at the end of the sintering process, and one of nitrogen, argon or helium is used as the protective gas throughout the sintering process; The weight distribution of the surface layer, middle layer and bottom layer materials in the sagger; The carbon content of the spray material A and the spray material B differs by 0.1% to 1%.
2. A method for sintering lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In the sintering environment, the volume ratio of the CO2 gas to the protective gas is 1:1-9.
3. A method for sintering lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The CO2 gas injection time is 2 to 6 hours in total.
4. A method for sintering lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The sintering temperature during the sintering process is 650-850° C., and the total sintering time is 7-12 hours.
5. A method for preparing lithium manganese iron phosphate positive electrode material, characterized in that: Take the LiMn x Fe (1-x) The iron source, manganese source, lithium source, doping source and carbon source in the stoichiometric ratio of PO4 (0.1≤x≤0.9) are placed in a ball mill, and after ball milling, they are transferred to a spray tower for spraying. By adjusting different carbon source contents, spray material A and spray material B are prepared respectively; The spray material A and the spray material B are sintered according to the sintering method for lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 4.
6. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: The carbon source is one or more of sucrose, glucose, citric acid, polypyrrolidone and PEG.
7. A positive electrode sheet, characterized in that: A pole piece prepared by using the positive electrode material prepared by the method for preparing lithium manganese iron phosphate positive electrode material according to claim 5 or 6.
